Character Building with Students in Learning Science Approach scientific - ,, Gusmaweti (LLDIKTI Wilayah X, 2014)
Building character, especially the younger generation of learners is very important and very urgent, if we look at the phenomena that occur and future challenges more complex. Characters such as honest, disimplin, obey the rules, responsibility, etc. are getting lost. The problems of this paper outlines